Energy conversion based on bio-inspired superwetting interfaces - Li,M; Li,C; Blackman,BRK; Saiz,E (Matter, 2021)
Bio-inspired superwetting interfaces can realize rapid transfer of liquid mass or momentum due to their unique surface structure and wetting characteristics. Combined with a suitably electrified material, these special interfaces can further promote the generation or transmission of electrons. Herein, we summarize the latest developments in water-energy collection technologies based on these interfaces, such as piezoelectric/triboelectric/pyroelectric nanogenerators. When it comes to harvesting energy generated by salinity gradients, reverse electrodialysis based on ion channels is now being widely investigated. We review the concept of “quantum-confined superfluids” on superwetting interfaces, and the conditions required to form a superfluid in molecular and ion channels. The applications of the superfluids in energy conversion are discussed, including the charging and discharging process of lithium batteries and harvesting salinity-gradient energy. This perspective identifies advantages, current challenges, and future directions in the development of energy-conversion devices using superwetting interfaces that could open the door to their broader application.